Formation and stability of gas-phase o-benzoquinone from oxidation of ortho-hydroxyphenyl: a combined neutral and distonic radical study. Issue 6 (28th October 2015) - Prendergast, Matthew B.; Kirk, Benjamin B.; Savee, John D.; Osborn, David L.; Taatjes, Craig A.; Masters, Kye-Simeon; Blanksby, Stephen J.; da Silva, Gabriel; Trevitt, Adam J.
Abstract : The o -hydroxyphenyl radical reacts with O2 to form o -benzoquinone + OH and cyclopentadienone is assigned as a secondary product. Abstract : Gas-phase product detection studies of o -hydroxyphenyl radical and O2 are reported at 373, 500, and 600 K, at 4 Torr (533.3 Pa), using VUV time-resolved synchrotron photoionisation mass spectrometry. The dominant products are assigned as o -benzoquinone (C6 H4 O2, m / z 108) and cyclopentadienone (C5 H4 O, m / z 80). It is concluded that cyclopentadienone forms as a secondary product from prompt decomposition of o -benzoquinone (and dissociative ionization of o -benzoquinone may contribute to the m / z 80 signal at photon energies ≳9.8 eV). Ion-trap reactions of the distonic o -hydroxyphenyl analogue, the 5-ammonium-2-hydroxyphenyl radical cation, with O2 are also reported and concur with the assignment of o -benzoquinone as the dominant product. The ion-trap study also provides support for a mechanism where cyclopentadienone is produced by decarbonylation of o -benzoquinone. Kinetic studies compare oxidation of the ammonium-tagged o -hydroxyphenyl and o -methylphenyl radical cations along with trimethylammonium-tagged analogues. Reaction efficiencies are found to be ca. 5% for both charge-tagged o -hydroxyphenyl and o -methylphenyl radicals irrespective of the charged substituent. G3X-K quantum chemical calculations are deployed to rationalise experimental results for o -hydroxyphenyl + O2 and its charge-tagged counterpart. The prevailing reaction mechanism, after O2 addition, involves a facile 1, 5-H shift in the peroxyl radical and subsequent elimination of OH to yield o -benzoquinone that is reminiscent of the Waddington mechanism for β-hydroxyperoxyl radicals. These results suggest o -hydroxyphenyl + O2 and decarbonylation of o -benzoquinone serve as plausible OH and CO sources in combustion.